Mewasiatkan Organ Tubuh sebagai Objek Wasiat Berdasarkan Fiqih Kontemporer - Lubis, Syahddan Dintara (ANWARUL, 2023)
This study discusses the review of juridical and Islamic law related to the field of medicine. There are several views of 'Fuqoha' scholars discussing the benefits of human organs as objects of wills based on contemporary fiqh. The research method used is normative juridical, which is a process to find a rule of law, legal principles and legal doctrines to answer the legal problems faced. The results show that selling human organs is not allowed, even in an emergency. However, scholars differ on the trade in human organs that are seen as "not living with dignity", such as people who have been decided dead, people who commit adultery muhshan or people who are apostates and wills in donating organs is permissible, because doing so will provide complete benefits to the community. others without causing any harm to himself.